On Nonlocal Neutral Stochastic Integro Differential Equations with Impulsive Random (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we discuss the existence and continuous dependenceon initial data of solutions for non-local random impulsive neutral stochasticintegrodifferential delayed equations. First, we prove the existence of mildsolutions to the equations by using Krasnoselskii's-Schaefer type fixed pointtheorem. Next, we prove the continuous dependence on initial data resultsunder the Lipschitz condition on a bounded and closed interval. Finally, wepropose an example to validate the obtained results.
Keywords: Existence; continuous dependence; random impulsive; integro differential equations; Krasnoselskii's-Schaefer type fixed point theorem.